Analysis of the effectiveness of the regulatory act "Regulations on the Railway Transport Safety Management System" - Oleksandr Pohorilyi (Збірник наукових праць Державного університету інфраструктури та технологій: серія "Транспортні системи і технології")
The article is devoted to a study that is quite rare in the scientific and technical literature. It is about analysing the impact of the regulatory document "Regulations on the Railway Transport Safety Management System" on the population groups and enterprises of Ukraine and its effectiveness after its approval. These two analyses are carried out before and after the approval of regulatory documents by state authorities (ministries, the Cabinet of Ministers, etc.). The relevance of this Regulation is explained by the need to implement European-type regulations in the activities of Ukrainian railways. The implementation is in line with the EU-Ukraine Association Agreement. The peculiarity of the Regulation in comparison with the existing one is explained by the fact that it becomes mandatory not only for JSC "Ukrainian Railways", but also for enterprises that use railway rolling stock and railway infrastructure in their activities. It was found that the railway transport sector includes 1517 enterprises. Based on the analysis of the impact of the Regulation on the Railway Traffic Management System on the interests of citizens, the state and business entities, a conclusion was made on the most rational option for achieving the goal of improving the level of railway traffic safety. The Regulation was approved by the Ministry of Infrastructure in 2021.